Kontribusi Keterampilan Membaca Pemahaman terhadap Keterampilan Menulis Teks Berita Siswa Kelas VII MTs Negeri 1 Kota Padang - Fitria, Annisa Sukma Dwi; Hafrison, Mohamad (TSAQOFAH, 2026)
This study was motivated by the importance of reading comprehension skills as a foundation for developing writing skills, particularly in news text writing, while empirical research that directly examines the contribution of reading comprehension to news text writing skills among madrasah students remains limited. The study aimed to (1) describe the news text reading comprehension skills of Grade VII students at MTs Negeri 1 Padang City, (2) describe their news text writing skills, and (3) analyze the contribution of reading comprehension skills to news text writing skills. This quantitative research employed a descriptive approach, with the population comprising all Grade VII students of MTs Negeri 1 Padang City in the 2024/2025 academic year. The sample consisted of 32 students selected using simple random sampling. The research instruments were an objective test of news text reading comprehension skills and a performance test of news text writing skills. Data were analyzed using descriptive statistics to determine the levels of reading and writing skills, and inferential statistics through t-tests and the coefficient of determination to examine the contribution of reading comprehension skills to news text writing skills. The findings indicate three main results: (1) the news text reading comprehension skills of Grade VII students at MTs Negeri 1 Padang City are in the “good” qualification; (2) their news text writing skills are in the “very good” qualification; and (3) there is a positive and significant relationship between reading comprehension skills and news text writing skills, as evidenced by the rejection of H₀ and acceptance of H₁, with the calculated t-value exceeding the t-table value. Based on the coefficient of determination, reading comprehension skills are shown to make a substantial contribution to students’ news text writing skills. These findings underscore the importance of strengthening reading comprehension instruction as a strategy to improve the quality of news text writing skills in Indonesian language learning at the madrasah tsanawiyah level.